PENDAMPINGAN LITERASI MASYARAKAT DALAM PENANGANAN STUNTING DAN WASTING DI DESA BESUK KECAMATAN KLABANG KABUPATEN BONDOWOSO - Yulia Tutik Nurfia; Saptono Hadi; Enggal Chairyadi Mulyono (LP2M Universitas Ibrahimy, 2022)
Lack of nutritional intake in pregnant women can result in low birth weight babies (LBW) and had an impact on malnutrition in toddlers. The problem lies in inadequate food intake, high poverty rates, low environmental sanitation, lack of food availability, poor parenting, and suboptimal health services which were the causes of inhibiting growth and development of infants and toddlers that are not in accordance with their age or called stunting. (short) and wasting (thin). This assistance involved the Besuk community, Bondowoso Regency, focusing on nutritional improvement-oriented counseling, as an effort to improve nutritional quality and bridge the understanding of parents in better parenting so as to reduce the risk of stunting and wasting. The lecture, discussion, question and answer method, practice and Problem Based Learning (PBL) models are applied as a step to invite active-creative foster partners to be innovative in handling foster babies, so that they have the competence and performance to face actual problems and or the reality of handling nutrition, infants, and children. pregnant women who are oriented towards parenting in a healthy environment. The results of the implementation of the service as a whole went smoothly and got a good response, so that the final achievement was that 12 foster caretakers (88.2%) understood the essentials of stunting and wasting, the remaining 11.75 needed guidance.